Template Synthesis of Three-Dimensional Cubic Ordered Mesoporous Carbon With Tunable Pore Sizes - Dai, Weijie (Springer, 2009)
Three-dimensional cubic ordered mesoporous carbons with tunable pore sizes have been synthesized by using cubic Ia3d mesoporous KIT-6 silica as the hard template and boric acid as the pore expanding agent. The prepared ordered mesoporous carbons were characterized by powder X-ray diffraction, scanning electron microscopy, transmission electron microscopy, and nitrogen adsorption–desorption analysis. The results show that the pore sizes of the prepared ordered mesoporous carbons with three-dimensional cubic structure can be regulated in the range of 3.9–9.4 nm. A simplified model was proposed to analyze the tailored pore sizes of the prepared ordered mesoporous carbons on the basis of the structural parameters of the silica template.